2010
DOI: 10.1155/2010/578604
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Underwater Robots with Electronic Nervous Systems

Abstract: We are developing robot controllers based on biomimetic design principles. The goal is to realise the adaptive capabilities of the animal models in natural environments. We report feasibility studies of a hybrid architecture that instantiates a command and coordinating level with computed discrete-time map-based (DTM) neuronal networks and the central pattern generators with analogue VLSI (Very Large Scale Integration) electronic neuron (aVLSI) networks. DTM networks are realised using neurons based on a 1-D o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…It was chosen as a true example of a synthetic organism and because it was funded and is in development, but further away from deployment than the others. Uses of the micro-robot were described for healthcare and environmental remediation, and the parts were described as coming from bacteria, yeast, and mammalian cells [38]. This case study was typed by the project team as “Unknown/Controllable” for its very high degree of novelty, but inability of the robots to self-replicate (like living genetically engineered organisms) and settings in which they deployed.…”
Section: Resultsmentioning
confidence: 99%
“…It was chosen as a true example of a synthetic organism and because it was funded and is in development, but further away from deployment than the others. Uses of the micro-robot were described for healthcare and environmental remediation, and the parts were described as coming from bacteria, yeast, and mammalian cells [38]. This case study was typed by the project team as “Unknown/Controllable” for its very high degree of novelty, but inability of the robots to self-replicate (like living genetically engineered organisms) and settings in which they deployed.…”
Section: Resultsmentioning
confidence: 99%
“…The individual neurons and synapses are instantiated as LabVIEW Virtual Instruments and connected by LabVIEW "wire" in the G Programming language. A complete explanation of the neuron and synapse equations and their software implementation has been previously described [30]. The DTM mathematical model is well suited for robotic implementation because it uses computationally-efficient difference equations that mimic neural dynamics rather than processor-intensive differential equations that model ionic conductances.…”
Section: Methodsmentioning
confidence: 99%
“…Advances in nonlinear dynamics [29,30] have yielded technologies that allow for the control of robots by synaptic networks in real time [1,23]. Controlling robots with neuronal and synaptic networks provides a powerful heuristic framework to compare and evaluate different hypothetical network topologies and candidate mechanisms for the control of behavior [2,43].…”
Section: Supported By Nsf Itr Expeditions Grant 0925751mentioning
confidence: 99%
“…Our studies have shown [1,43] that numerical simulations of networks needed to control a biomimetic robot can be implemented in real time using standard microprocessors. The hardware layout for the helicopter control system is shown in Figure 1.…”
Section: Helicopter Platformmentioning
confidence: 99%
See 1 more Smart Citation